Building Trust: Key to Improve Knowledge Sharing - Debata, Bikash Ranjan; Sreekumar (Gyan Management Journal, 2008)
The knowledge transaction is anticipated as the basic device byhich knowledge is communal within organizations. This model is developed drawing collectively literature on knowledge markets transaction cost economics and theories of knowledge. Five categorie of factors influencing kno wledge transactions were identified as: intrinsic motivation, authority, trust price and technology. Of these factors, trust was found to be the most important factor in fostering knowledge sharing. Trust betw en individual nables knowledg transactions to be executed efficiently by relying on the person’s word. Conversely the ex is ten c of dis tr us t is a powerful inhibitor for knowledg sharing.